PENGARUH PENERAPAN MODEL PROBLEM BASED LEARNING DAN MOTIVASI BERPRESTASI TERHADAP HASIL BELAJAR SISWA KELAS V DALAM MATA PELAJARAN MATEMATIKA - Lauhil Mahfuzh Isman; Hari Karyono; Endang Mastuti Rahayu (Elementary School Teacher Education (PGSD), STKIP PGRI Sumenep, 2021)
This study aims to determine the effect of applying Problem Based Learning model and achievement motivation on the learning outcomes of fifth grade students. The research method used in this study is a quantitative method with two-variant analysis techniques. This type of research is experimental research. The subjects of this study were the fifth grade students fo SDN Jemundo 1, totaling 25 students as the experimental group and the fifth grade students of SDN Sadang, totaling 24 students as the control group in the 2020/2021 school year. The results of this study are (1) there is an effect of applying Problem Based Learning (PBL) model (mean of 81.24) and conventional learning (mean of 79.20) on the Mathematics subject of fifth grade students of SDN Taman sub-district Sidoarjo where PBL model is more effective with a significance value of 0.000. (2) there is an influence of achievement motivation on learning outcomes where students with high achievement motivation (mean value 81.46) are superior to students with low achievement motivation (mean value 78.63) with a significance value of 0.001. (3) there is an interaction between the application of PBL model and achievement motivation on learning outcomes with a significance value of 0.001. Thus, problem based learning model and achievement motivation can effect student leaning outcomes in mathematics. Keywords: Problem Based Learning (PBL) model, Achievement Motivation, Outcome of Learning